Causes of and remedies for the people's Republic of China's external imbalances: The role of factor market distortion - Yiping Huang; Kunyu Tao (Asian Development Bank Institute (ADBI), 2011)
The current account surplus of the People's Republic of China (PRC) has drawn much foreign and domestic attention. This paper focuses on the reasons and remedies for the PRC's current account surpluses. Rather than deploying the standard explanations, we argue that asymmetric market liberalization and the related factor market distortion is the root reason for the PRC's external imbalances. These cost distortions have artificially lowered PRC production costs, raised profits, and improved their products' international competitiveness which has not only stimulated the economy, but also brought about severe structural risks. We completed a crude estimation for factor cost distortions in the PRC during 2000-2009 which matched its current account surpluses quite well. In order to rebalance the economy, we recommend that the PRC should adopt a comprehensive reform package focusing on removing the factor market distortions.
Keywords: F32; O11; H24; E61; 330; Zahlungsbilanzungleichgewicht; Kausalanalyse; China